Winner Clean Coal - Restoring Coal's Sheen. - Sweet, W. (IEEE spectrum)
In this paper, a Swedish energy company takes a novel approach to carbon capture. An oxyfuel pilot plant is investigated to show that burning coal in an atmosphere of pure oxygen can facilitate carbon capture; to evaluate technical features and economics for lignite and bituminous coal.